Intersection curve of two parametric surfaces in Euclidean n-space - Duldul, Mustafa; Ozcetin, B. Merih (UNIV TARTU PRESS, 2021)
The aim of this paper is to study the differential geometric properties of the intersection curve of two parametric surfaces in Euclidean n-space. For this aim, we first present the mth order derivative formula of a curve lying on a parametric surface. Then, we obtain curvatures and Frenet vectors of the transversal intersection curve of two parametric surfaces in Euclidean n-space. We also provide computer code produced in MATLAB to simplify determining the coefficients relative to Frenet frame of higher order derivatives of a curve.
Keywords: Surface-surface intersection; transversal intersection; Frenet vectors; curvatures; DIFFERENTIAL GEOMETRY; HYPERSURFACES; CURVATURE; FORMULAS; R-4; Mathematics